Epitopes of HERV-Wenv induce antigen-specific humoral immunity in multiple sclerosis patients - Mameli, Giuseppe; Cossu, Davide; Cocco, Eleonora; Frau, Jessica; Marrosu, Maria Giovanna; Niegowska, Magdalena; Sechi, Leonardo Antonio (Journal of neuroimmunology, 2015)
To verify the serological response mounted against antigenic peptides from HERV-Wenv protein, we analyzed 80 multiple sclerosis (MS) serum samples, 27 of which were re-analyzed after a 6-month follow-up IFN-β therapy, and 73 healthy controls. Indirect ELISAs were carried out to detect antibodies specific for all the synthetic peptides derived from HERV-Wenv. Two antigenic peptides, HERV-Wenv93–108 (31.25%, p<0.0001) and HERV-Wenv248–262 (15%, p=0.02), were highly recognized by MS patients' antibodies when compared to healthy subjects. Moreover, antibody titer against these two peptides slightly decreased after six months of IFN-β-based therapy. •Six antigenic peptides from HERV-Wenv protein were identified.•A peptide-based indirect ELISA was used to screen a population of 80 MS and 73 HCs.•Only two peptides were capable of inducing a strong humoral response in MS subjects.•Antibody values against these two peptides decreased after six months of IFN-β therapy.